In the Hegemon's shadow : leading states and the rise of regional powers - Montgomery, Evan Braden (Cornell studies in security affairs., 2016)
The relationship between established powers and emerging powers is one of the most important topics in world politics. Nevertheless, few studies have investigated how the leading state in the international system responds to power shifts in peripheral regions-actors that are not yet and might never become great powers but that are still increasing their strength, extending their influence, and trying to reorder their corner of the world. This work fills this gap, and draws on different strands of realist theory to develop a novel framework that explains why leading states have accommodated some rising regional powers but opposed others.